High nutrient loading and climatic parameters influence the dominance and dissimilarity of toxigenic cyanobacteria in northern bays of Lake Victoria - Olokotum, Mark; Troussellier, Marc; Escalas, Arthur; Hamlaoui, Sahima; Okello, William; Semyalo, Ronald; Humbert, Jean-François; Bernard, Cécile (Journal of Great Lakes Research, 2021)
Eutrophication of Lake Victoria led to changes in its phytoplankton communities. However, different levels of eutrophication exist in the open lake and the bays, and between embayments. This study utilized spatial and temporal sampling of Napoleon Gulf and Murchison Bay, exhibiting different trophic conditions. Over one year, we investigated phytoplankton biomass, richness, diversity and dissimilarity, and related the dynamics of the dominant species to the limnological and climatic conditions. The results confirmed that Napoleon Gulf and Murchison Bay showed large differences in eutrophication status, with lower nutrient concentrations in Napoleon Gulf than in Murchison Bay, where a strong gradient was observed from inshore to offshore areas. These nutrient dynamics resulted in a 4 to 10 fold higher chlorophyll-a in Murchison Bay than in Napoleon Gulf. From the embayments, 135 phytoplankton taxa were recorded with no significant differences in alpha diversity. However, high dissimilarity in community structure was observed in beta diversity, mostly due to a turnover among the dominant toxigenic species. Thus, from a similar species pool, there was a shift in the dominant toxigenic cyanobacteria from Microcystis flos-aquae and M. aeruginosa in Murchison Bay, Dolichospermum circinale and Planktolyngbya circumcreta in Napoleon Gulf to D. circinale in the offshore stations. These cyanobacteria are toxigenic taxa with known health hazards. Using partial least square models, we showed that both climatic variables (e.g. wind, solar radiation) and levels of inorganic dissolved nutrients (e.g. SRP, NO3 – , and NH4 + ) are the main drivers of differences and dominance in cyanobacteria communities in northern Lake Victoria.
Keywords: Eutrophication; Lake Victoria; Cyanobacteria; Phytoplankton; Diversity; Bays and gulfs